Penggunaan Semut Hitam dan Bokashi dalam Peningkatan Resistensi dan Produksi Tanaman Kakao - Armaniar Armaniar; Ahamad Saleh; Fachrina Wibowo (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Cocoa is the source of life for more than 6.5 million farming families. Cocoa farmers in Langkat District about 2081 with an area of 2603/ha. Cocoa production in Langkat recorded about 950 kg/ha/year, but some produced about 450 kg/ha/year. In addition to the shortage of subsidized inorganic fertilizers, another problem in Indonesia’s low cocoa production especially Langkat is because cultivation was not done.Another, the attack of plant-disturbing organisms, such as Cocoa Borer (CPB) and Vascular Streak Dieback (VSD). Cocoa pod borer, Conopomorpha cramerella is a very serious pest and 80% production reduced. It was because the cocoa pod borer is difficult to control and had spread throughout Langkat. By 2018, cocoa production in Langkat about 7 kg/weeks. Biological control using black ants has been developed as a natural CPB pest agency by making ant nest of 30-40 strands of dried cocoa leaves with permanent polystyrene plastic or dry cocoa leaves and tied with rafia straps. The results showed that cocoa pods were heavy damaged under 5%. Fertilizing with Bokashi which are made of cocoa leaves, bran, husks and manure fermented with EM-4 was applied 5 kg/tree, for plant resistance to VSD disease and cocoa production increased. Farmer are commitment to their respective cocoa gardens and hope they can produce organic cocoa in the future